HASIL BELAJAR KETERAMPILAN PROSES SAINS SISWA MELALUI PENERAPAN MODEL DISCOVERY LEARNING KELAS XI MIPA SMAN 15 PEKANBARU - Vinni Fitri Anita; Syahril Syahril; Zulhelmi Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Science process skills are the skills needed to acquire, develop, and apply concepts, laws, and theories of science, both in the form of mental skills, physical skills (manual) and social skills. This study aims to describe the learning outcomes of students' science process skills by applying discovery learning learning models. The research subjects were students of class XI MIPA 2 SMAN 15 Pekanbaru. This type of research is a Pre-Experimental design with a one shot case study design. This research instrument as many as 19 multiple choice questions. Data is collected by providing a test of science process skills to the subject. Data were analyzed descriptively to provide a picture of the learning outcomes of students' science process skills including student absorption and learning effectiveness on the material elasticity and hooke law. The results obtained were the average absorption of students namely 78.22% in the good category. Thus, it can be concluded that the application of discovery learning model is effective for training science process skills of class XI students of SMA Negeri 15 Pekanbaru on material elasticity and hooke law.Key Words: Discovery Learning Model, The Results Of Learning Process Skills,Elasticity And Hooke Law